2015
DOI: 10.1111/ijfs.12817
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phenolic profiles and antioxidant potentials of the leaves and seeds of Thai holy and sweet basils

Abstract: Eight phenolics rosmarinic, caftaric, caffeic, chicoric, p-hydroxybenzoic, p-coumaric, protocatechuic acid and rutin were identified in Thai holy/sweet basil leaves or seeds. The overall phenolics in THBL were two, three and twenty times higher than that in TSBL, THBS and TSBS, respectively. Oppositely, the TP content of TSBL was one and a half times higher than THBL which was followed by THBS and TSBS. The order of scavenging DPPH free radical activity from high to low was THBL, TSBL, THBS and TSBS and consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
0
12
2
Order By: Relevance
“…The TPC reported by Shen et al (2015) was 304.01 AE 12.46 mg CE per g DW and 10 mg CE per g DW for wild leaves and seeds, respectively. 40 These values are much lower than our ndings because in in vitro cultures various PGRs are responsible for secondary metabolites enhancement. The total phenolic production associated with DW was found to be maximum (365.05 mg L À1 ) in response to 9.0 mM TDZ, whereas the other PGR concentrations resulted in lower values (Fig.…”
Section: Determination Of Biomass Accumulation In Callus Culturecontrasting
confidence: 61%
“…The TPC reported by Shen et al (2015) was 304.01 AE 12.46 mg CE per g DW and 10 mg CE per g DW for wild leaves and seeds, respectively. 40 These values are much lower than our ndings because in in vitro cultures various PGRs are responsible for secondary metabolites enhancement. The total phenolic production associated with DW was found to be maximum (365.05 mg L À1 ) in response to 9.0 mM TDZ, whereas the other PGR concentrations resulted in lower values (Fig.…”
Section: Determination Of Biomass Accumulation In Callus Culturecontrasting
confidence: 61%
“…Lagouri and Nisteropoulou () previously reported that rosmarinic acid was a slightly stronger reducing agent than vitamin C (EC 50 = 0.0022 and 0.0033, respectively). Hence, other phenolic compounds in the crude extracts, such as chicoric acid, protocatechuic acid, caftaric acid, and p ‐hydroxybenzoic acid, might be responsible for the FRAP reducing power in this case (Lee, ; Shen, Prinyawiwatkul, Lotrakul, & Xu, ). These results supported the authors' hypothesis that crude extracts from sweet basil leaves have a potential to protect vitamin C.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant capacity was measured as the decrease in absorbance at 517 nm in a UV-visible SpectraMax Plus384 spectrophotometer (Shen et al, 2015). The DPPH solution (0.01 mM, 1.8 mL) was mixed with 0.2 mL of each petal extract in spectrophotometric cuvettes.…”
Section: Determination Of Dpph Antioxidant Activitymentioning
confidence: 99%